General Comparison of FY-4A/AGRI With Other GEO/LEO Instruments and Its Potential and Challenges in Non-meteorological Applications - Zhang, Peng; Zhu, Lin; Tang, Shihao; Gao, Ling; Chen, Lin; Zheng, Wei; Han, Xiuzhen; Chen, Jie; Shao, Jiali (Frontiers in Earth Science, 2019)
Meteorological satellites have become an irreplaceable tool for weather and land observation. Traditionally, geo-stationary satellites are commonly used in operational meteorological services due to their high temporal resolution properties. While polar-orbiting satellites, with their high spatial resolution properties, are more applied to monitor environmental change and natural disasters. The development of China’s next-generation geostationary meteorological satellites (FY-4 series) represents an exciting expansion in Chinese Non-meteorological remote sensing capabilities. The first satellite (FengYun-4A) of the FY-4 series was launched on 11 December 2016. The Advanced Geosynchronous Radiation Imager (AGRI) on board FY-4A has 14 spectral bands (increased from the five bands of FY-2) that are quantized with 12 bits per pixel (up from 10 bits for FY-2) and sampled at 1 km at nadir in the visible (VIS), 2 km in the near-infrared (NIR), and 4 km in the remaining IR spectral bands (compared with 1.25 km for VIS, no NIR, and 5 km for IR of FY-2). For the following series of FY-4A, the AGRI channel number will be gradually increased from 14 to 18 with IR spatial resolution of 2 km, and the full-disc temporal resolution will be enhanced from 15 to 5 min. With their improved spectral, spatial and temporal resolution properties, the FY-4 series will gradually approach the LEO sensors in spatial and spectral resolutions, which will offer greater opportunities and capacities for observing fine objects and rapid change of land, ocean and atmosphere. This review paper provides an introduction to the Chinese FY-4 observation capabilities, comparison of FY-4 with other new generation geo-stationary weather satellites, and associated non-meteorological applications. A series of typical examples based on recent and on-going operational work in NSMC/CMA that are using FY-4A data for non-meteorological applications were demonstrated and discussed, including (i) Aerosol monitoring; (ii) Sand storm monitoring; (iii)Volcanic ash detection and aviation applications ; (iv) Fire detection and dynamical evaluation; (v) Water body detection and (vi) Cyanobacterial Blooms monitoring. The paper concludes with a synthesis of these application areas and challenges we have to address for future research, technological innovation and in-depth applications.